Controlling droplet impact velocity and droplet volume: key factors to achieving high cell viability in sub-nanoliter droplet-based bioprinting - Ng, Wei Long (2022)
Three-dimensional (3D) bioprinting systems serve as advanced manufacturing platform for the precise deposition of cells and biomaterials at pre-defined positions. Among the various bioprinting techniques, the drop-on-demand jetting approach facilitates deposition of pico/nanoliter droplets of cells and materials for study of cell-cell and cell-matrix interactions. Despite advances in the bioprinting systems, there is a poor understanding of how the viability of primary human cells within sub-nanoliter droplets is affected during the printing process. In this work, a thermal inkjet system is utilized to dispense sub-nanoliter cell-laden droplets, and two key factors - droplet impact velocity and droplet volume - are identified to have significant effect on the viability and proliferation of printed cells. An increase in the cell concentration results in slower impact velocity, which leads to higher viability of the printed cells and improves the printing outcome by mitigating droplet splashing. Furthermore, a minimum droplet volume of 20 nL per spot helps to mitigate evaporation-induced cell damage and maintain high viability of the printed cells within a printing duration of 2 min. Hence, controlling the droplet impact velocity and droplet volume in sub-nanoliter bioprinting is critical for viability and proliferation of printed human primary cells.